British Expedition to Kalat, 1948 and 1957 - de Cardi, Beatrice (1964)
for sites discovered during 1948 and 1957 see map p. 21: Kile Gul Mohammed, Anjira, Alizai – Nindo-damb, Kinneru, Phusi – Singenkalat – Pathani-damb.